Tytuł profesora w Polsce w latach 1920–1990. Część 1. Warunki przyznawania tytułu profesora w prawie szkół wyższych - Wojtczak, Krystyna (Studia Prawa Publicznego, 2019)
The Polish law on schools of higher education of the past years did not provide a uniformed deﬁ nition of the institution of the title of professor. Diff erences in its treatment generally corresponded to the legal and factual conditions in which the institutions of higher education were operating in interwar Poland in the ﬁ rst years of the Polish People’s Republic. This was not a period of simple change. The ﬁ rst establishments of higher education operating after 1918, and also after the end of World War II, were struggling not only with the acquisition of professors. Later years, despite the opening of new schools of higher education, did not manage to solve the problem of professorship shortages. What was more, a new threat emerged that was ideologisation of universities and scientiﬁ c research. Gradually ideological assumptions had become the criteria of professorship selection. This state of aff airs changed only as a result of the political transformation after 1989. In the interwar Poland and the ﬁ rst years of the Polish People’s Republic, the law provided for two titles of professor: extraordinary and ordinary. A special position was also given to honorary professors, and the award of other professorships was not an isolated act. The shortage of professorship staff was compensated by awarding titles of titular professor, contract professor and deputy professor. This solution continued to prevail in the early years of the Polish People’s Republic and changed only in 1952 when the Act of 1951 came into force. It provided for two scientiﬁ c titles: the extraordinary professor and the ordinary professor. The Act of 1958 Act extended their number by including the titles of contract professor and deputy professor and speciﬁ ed other conditions for awarding these titles. The article presents legal solutions of the past years not only in the scope in which they served the selection of professors’ staff and the conditions of scientiﬁ c advancement set for them in particular years, as well as the conditions in which these advancements were possible.